1995
DOI: 10.1177/014662169501900206
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Correlated Errors on Generalizability and Dependability Coefficients

Abstract: This study investigated the effects of correlated errors on the person x occasion design in which the confounding effect of equal time intervals results in correlated error terms in the linear model. Two specific error correlation structures were examined: the first-order stationary autoregressive (SARI), and the first-order nonstationary autoregressive (NARI) with increasing variance parameters. The effects of correlated errors on the existing generalizability and dependability coefficients were assessed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Our conclusions fully coincide with the results found by Smith and Luecht (1992) and Bost (1995) in their study about the effect of ignoring a stationary correlated error structure on the estimation of the G-coefficients. This misspecification can seriously affect both, the point estimates of the reliability parameters and the inferential procedures related to T R and Λ R .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our conclusions fully coincide with the results found by Smith and Luecht (1992) and Bost (1995) in their study about the effect of ignoring a stationary correlated error structure on the estimation of the G-coefficients. This misspecification can seriously affect both, the point estimates of the reliability parameters and the inferential procedures related to T R and Λ R .…”
Section: Discussionsupporting
confidence: 92%
“…These findings fully coincide with the results reported by Smith and Luecht (1992) and Bost (1995) in their studies of the effect of ignoring a stationary correlated error structure on the estimation of the G-coefficients. Fortunately, unlike in the modeling framework used in G-theory, linear mixed models allow for the absorption of such a correlation structure.…”
Section: R Rsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, the univariate G-theory literature has suggested that unaccounted for covariances among residual effects would lead to inflated estimates of person main effect variance and to underestimates of residual variance (e.g., Bost, 1995;Smith & Luecht, 1992). The effects predicted by the work of these researchers, coupled with Box's (1954) earlier work, would also suggest that unaccounted for covariance among other sources of observed variance (e.g., Person  Trait and Person  Method interaction effects) would lead to inflated estimates of person main effects in the context of applying a univariate G-theory model to MTMM data because it would be the person main effect term that is relied upon to account for such covariance.…”
Section: A G-theory-based Process For Modeling Mtmm Datamentioning
confidence: 99%
“…Similar results have been found for g-theory designs with multiple time points. In such designs, underestimation was present for uncorrelated errors with increasing variances over time, overestimation was present for correlated errors with equal variances over time, and both directions of estimation bias were present for correlated errors with unequal variances over time (Bost, 1995). It is important to note that correlated errors may arise for a variety of reasons.…”
Section: Estimators Of the Reliability Coefficient And Their Propertiesmentioning
confidence: 99%